Den Danske Ordbog på nettet – en undersøgelse af version 3.0 - Farø, Ken; Vinther Jensen, Lene (LexicoNordica, 2018)
This review article takes a selective look at the electronic corpusbased Danish dictionary Den Danske Ordbog. We aim at a descriptive and critical – yet fair – analysis of this major pioneering work within Danish monolingual lexicography. Focusing on the online version and some of its new features, we try to find out whether this lexical tool meets the needs in terms of coverage of both recent and more general lexis. We also suggest a new way to perceive corpus-based dictionaries and the possible consequences of their inclusion policies.